Improving feedforward controls to improve NPD portfolio performance – an empirical study - Baker, Mark H.; Bourne, Mike (Case Western Reserve University: Weatherhead School of Management, 2022)
Managers making crucial project selections in large, fast-changing project portfolios face the challenge of balancing the tension between control (performance) and creativity (experimentation/innovation). To better manage this challenge and to improve performance, some practitioners and scholars have considered the application of more sophisticated feedforward controls in new product development portfolio project selections. However, empirical studies of changes in the sophistication of such controls and of their influence on performance are lacking. We use an engaged scholarship approach and an action research methodology in a large international organization with multiple business units to study the post-intervention changes in applied controls and changes in portfolio performance. Our findings identify the underlying generative mechanisms influencing the changes in the applied sophistication of feedforward controls, how these changes enable portfolio managers to better balance the tension between control and creativity in project selection, and the performance outcomes.